Aerobic Exercise Training Improves Microvascular Function and Oxidative Stress Parameters in Diet- Induced Type 2 Diabetic Mice - Rodrigues, Karine Lino (2022)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Investigação Cardiovascular. Rio de Janeiro, RJ, Brasil.